A study of antipsychotic drug use in nursing homes: epidemiologic evidence suggesting misuse. - Ray, W A (1980)
We reviewed 384,326 prescriptions for 5,902 Medicaid patients residing continuously for one year in 173 Tennessee nursing homes. Of these patients, 43 per cent received antipsychotic drugs; 9 per cent were chronic recipients (received at least 365 daily doses per year). Of the 1,580 physicians who cared for these patients, 42 per cent prescribed antipsychotic medication. Physicians with large nursing home practices (10 or more patients) prescribed 81 per cent of the total antipsychotic medication, and were usually family practitioners (78 per cent) and in rural practice (47 per cent). As nursing home practice size increased, doctors prescribed more drug per patient (p less than .001). Wide variation in antipsychotic drug use occurred among nursing homes; the chronic recipient rate ranged from 0 to 46 per cent. More drug was given per patient in larger homes (r = .18, p less than .05). Typically, one physician (the "dominant" physician) provided care for the majority of a nursing home's patients. The proportion of a home's patients seen by the dominant physician was correlated with the chronic recipient rate (r = .17, p less than .05). These findings provide epidemiologic evidence suggesting misuse of antipsychotic drugs in nursing homes. They illustrate the need for investigations of techniques for patient management in nursing homes which rely less upon psychtropic drugs.